1997
DOI: 10.3171/jns.1997.87.3.0420
|View full text |Cite
|
Sign up to set email alerts
|

Role of glial filaments in cells and tumors of glial origin: a review

Abstract: In the adult human brain, normal astrocytes constitute nearly 40% of the total central nervous system (CNS) cell population and may assume a star-shaped configuration resembling epithelial cells insofar as the astrocytes remain intimately associated, through their cytoplasmic extensions, with the basement membrane of the capillary endothelial cells and the basal lamina of the glial limitans externa. Although their exact function remains unknown, in the past, astrocytes were thought to subserve an important sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(67 citation statements)
references
References 105 publications
3
63
0
1
Order By: Relevance
“…Immunocytochemical analysis (Fig. 4A) shows that nearly all the cells stained positively for GFAP, a marker for brain astrocytes (32), and negatively for fibronectin and myelin basic protein, which are markers of fibroblasts and oligodendrocytes, respectively (31). Western blot analysis confirmed that the primary astrocytes from wild-type, Glc-6-Pase-␣ Ϫ/Ϫ , or Glc-6-PT Ϫ/Ϫ pups express GFAP (Fig.…”
Section: Fig 2 Expression Of Glc-6-pase-␤ and Glc-6-pt In The Brainmentioning
confidence: 74%
See 1 more Smart Citation
“…Immunocytochemical analysis (Fig. 4A) shows that nearly all the cells stained positively for GFAP, a marker for brain astrocytes (32), and negatively for fibronectin and myelin basic protein, which are markers of fibroblasts and oligodendrocytes, respectively (31). Western blot analysis confirmed that the primary astrocytes from wild-type, Glc-6-Pase-␣ Ϫ/Ϫ , or Glc-6-PT Ϫ/Ϫ pups express GFAP (Fig.…”
Section: Fig 2 Expression Of Glc-6-pase-␤ and Glc-6-pt In The Brainmentioning
confidence: 74%
“…The purity of the astrocytes was determined by staining for GFAP (32). The cells were fixed for 10 min in 4% paraformaldehyde, incubated for 30 min at room temperature in TST buffer (0.05 M Tris-HCl, pH 7.5, 0.15 M NaCl, and 0.1% Triton-X-100) containing 1% bovine serum albumin (BSA) and 10% horse serum (TST-BSA), and then incubated overnight at 4°C with a rabbit anti-GFAP antibody at 4 g/ml in TST-BSA.…”
Section: Construction Of Recombinant Adenoviral Mouse Glc-6-pase-␤-mentioning
confidence: 99%
“…Glial cells are the predominant cell type in the brain, constituting more than 50% of the total cell count and outnumbering neurons 10-fold (Pope, 1978;Rutka et al, 1997). Two major subtypes of glia are distinguished by their distinct functions in the nervous system: oligodendrocytes, which form myelin sheaths around nerve cell axons, and astrocytes, which maintain brain homeostasis and respond to pathogens and brain injury (Benveniste, 1992;Verkhratsky et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Müller cells play a central role in retinal repair processes after injury. In particular, GFAP is involved in cell adhesion mechanisms, interacting with the cytoskeleton, surface receptors, and extracellular matrix in glia [23,[35][36][37]. In addition, the formation of epiretinal traction involves intraretinal glial proliferation, which hitherto has been considered predominantly epiretinal [38].…”
Section: Discussionmentioning
confidence: 99%
“…The contraction of this tissue induces centripetal tangential traction upon the underlying retinal layers, producing changes in the inner and outer layers. [22][23][24][25][26][27][28] Although the pathogenesis appears to be epiretinal, macular changes are not confined to the vitreomacular interface (VMI). Recent studies have hypothesized that iERM may induce intraretinal changes due to the tangential vector forces associated with the expression rate of glial fibrillary acid protein (GFAP).…”
Section: Introductionmentioning
confidence: 99%